Association of diabetes and kidney function according to age and systolic function with the incidence of sudden cardiac death and non‐sudden cardiac death in myocardial infarction survivors with heart failure. (2nd September 2019) - Coiro, Stefano; Girerd, Nicolas; Sharma, Abhinav; Rossignol, Patrick; Tritto, Isabella; Pitt, Bertram; Pfeffer, Marc A.; McMurray, John J.V.; Ambrosio, Giuseppe; Dickstein, Kenneth; Moss, Arthur; Zannad, Faiez
Abstract: Aims: An implantable cardioverter‐defibrillator (ICD) is recommended for reducing the risk of sudden cardiac death (SCD) in myocardial infarction (MI) patients with a left ventricular ejection fraction (LVEF) ≤ 30%, as well as patients with a LVEF ≤ 35% and heart failure symptoms. Diabetes and/or impaired kidney function may confer additional SCD risk. We assessed the association between these two risk factors with SCD and non‐SCD among MI survivors taking account of age and LVEF. Methods and results: A total of 17 773 patients from the High‐Risk MI Database were evaluated. Overall, diabetes and estimated glomerular filtration rate < 60 mL/min/1.73 m 2, individually and together, conferred a higher risk of SCD [adjusted competing risk: hazard ratio (HR) 1.23, 1.23, and 1.32, respectively; all P  < 0.03] and non‐SCD (HR 1.34, 1.52, and 2.13, respectively; all P  < 0.0001). Annual SCD rates in patients with LVEF > 35% and with diabetes, impaired kidney function, or both (2.0%, 2.5% and 2.7%, respectively) were comparable to rates observed in patients with LVEF 30–35% but no such risk factors (1.7%). However, these patients had also similarly higher non‐SCD rates, such that the ratio of SCD to non‐SCD was not increased. Importantly, this ratio was mostly dependent on age, with higher overall ratios in youngest subgroups (0.89 in patients < 55 years vs. 0.38 in patients ≥ 75 years), regardless of risk factors. Conclusion: Although MI survivors with LVEF > 35% with diabetes, impaired kidney function, or both are at increased risk of SCD, the risk of non‐SCD risk is even higher, suggesting an extension of the current indication for an ICD to them is unlikely to be worthwhile. MI survivors with low LVEF and aged < 55 years are likely to have the greatest potential benefit from ICD implantation.